A fast stitching method based on verticality calibration using three marker points. Issue 18 (24th October 2019) - Huang, Chunzhi; Fu, Yanjun; Zhong, Kejun; Cai, Xiaoqi; Guan, Bingliang
ABSTRACT: The speed of three-dimensional (3D) reconstruction based on structured light is affected by the stitching speed. In order to improve the stitching speed, a fast stitching method based on verticality calibration is proposed. Firstly, vertical calibration is used to place the camera perpendicular to the reference plane; then, the rotation axis is corrected. A normal vector of a plane based on three marker points is determined, and the decomposition vector perpendicular to the corrected rotation axis is obtained. Secondly, the angle between the decomposition vector before and after transformation is calculated. Finally, the rotation (R) matrix and translation (T) matrix are solved, and the stitching is completed. Experiments show that this method can improve the speed of surface stitching in 3D reconstruction based on structured light. The average error of stitching is 0.1103 mm and the standard deviation is 0.0327 mm when the stitching area is 250 mm × 90 mm.